LENTERA QALBU SEBUAH PROGRAM DAKWAH RADAR TV PALU - Abdullah Abdullah; Nurdin Nurdin (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2017)
This paper discusses the role of Radar TV Palu in spreading Islam. As a medium of da’wah (Islamic propagation), Radar TV is very concerned with the mission of Islamic da’wah so that programs of da’wah were made optimal to reach the audience especially those who are Muslims. To that end, Radar TV produces Lentera Qalbu as a program of da’wah, which becomes a medium for the Muslim community of Palu and its surrounding areas to study Islam. In addition, broadcasting programs of da’wah provides another alternative that can eliminate the saturation of the community due to flood of entertainment programs that tend to be contradictory to da’wah mission.